Pyrethrum (Tanacetum cinerariifolium) from the northern Adriatic as a potential source of natural insecticide - Ambrožič-Dolinšek, Jana (Annales. Series historia naturalis, 2007)
Pyrethrum Tanacetum cinerariifolium (Trevir.) Schulty-Bip., a species native to the Eastern Adriatic coastal mountains and islands, is a plant widely used in the production of natural insecticides, pyrethrins. The biosynthetic potential of Pyrethrum from two different locations in the Northern Adriatic for pyrethrin production was determined. In all the samples obtained, all 6 pyrethrins were detected, as measured by HPLC. The highest pyrethrin content was detected in the flower heads, which contained, on average, 1.2 % pyrethrins of dry weight. The pyrethrin content of flower heads from the Northern Adriatic populations is comparable with the content levels in conventional production of Pyrethrum, but not as high as the content levels for highly productive Pyrethrum clones from countries currently producing pyrethrins.
Keywords: bolhač; HPLC; piretrini; severni Jadran; Tanacetum cinerariifolium